PENGARUH PERBANDINGAN AMPAS KOPI DAN PUPUK KANDANG TERHADAP PERTUMBUHAN TANAMAN CABAI MERAH (Capsicum annuum L.) - Mardatillah, Annisa; Herlina, Nofripa; Irma, Wirdati Irma (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2026)
Red chili (Capsicum annuum L.) is one of Indonesia’s major horticultural commodities with high economic value and an essential role in national food security. Farmers’ dependence on chemical fertilizers in the long term can reduce soil fertility and cause environmental pollution; therefore, environmentally friendly and cost-effective organic fertilizer alternatives are needed. This study aimed to analyze the effect of coffee grounds and manure ratio on the growth of red chili plants and to determine the optimal combination that supports the best vegetative performance. The research was conducted as a field experiment using a Completely Randomized Design (CRD) consisting of six treatments with three replications, namely combinations of coffee grounds and manure (P1 = 50:0 g; P2 = 40:10 g; P3 = 30:20 g; P4 = 0:20 g; P5 = 5:15 g; P6 = 10:10 g). Growth parameters observed included plant height and number of leaves, measured weekly for four weeks. Data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney test. The results showed that the combination of 30 g coffee grounds and 20 g manure (P3) produced the highest plant height, while 40 g coffee grounds and 10 g manure (P2) resulted in the greatest number of leaves. A balanced ratio of coffee grounds and manure improved soil structure and nutrient availability, thus supporting optimal vegetative growth of red chili plants.